Behavior of Rectangular-Sectional Steel Tubular Columns Filled with High-Strength Steel Fiber Reinforced Concrete Under Axial Compression - Liu, Shiming (Materials (Basel), 2019)
This paper studies the effect of high-strength steel fiber reinforced concrete (SFRC) on the axial compression behavior of rectangular-sectional SFRC-filled steel tube columns. The purpose is to improve the integrated bearing capacity of these composite columns. Nine rectangular-sectional SFRC-filled steel tube columns and one normal concrete-filled steel tube column were designed and tested under axial loading to failure. The compressive strength of concrete, the volume fraction of steel fiber, the type of internal longitudinal stiffener and the spacing of circular holes in perfobond rib were considered as the main parameters. The failure modes, axial load-deformation curves, energy dissipation capacity, axial bearing capacity, and ductility index are presented. The results identified that steel fiber delayed the local buckling of steel tube and increased the ductility and energy dissipation capacity of the columns when the volume fraction of steel fiber was not less than 0.8%. The longitudinal internal stiffening ribs and their type changed the failure modes of the local buckling of steel tube, and perfobond ribs increased the ductility and energy dissipation capacity to some degree. The compressive strength of SFRC failed to change the failure modes, but had a significant impact on the energy dissipation capacity, bearing capacity, and ductility. The predictive formulas for the bearing capacity and ductility index of rectangular-sectional SFRC-filled steel tube columns are proposed to be used in engineering practice.